High-Permittivity Dielectric Half-Loop Yagi-Uda Antenna With End-Fire Radiation - Wen Zheng; Shiyan Wang; Mengjiao Tang; Gang Zhang; Wang Ren; Changzhou Hua (IEEE Open Journal of Antennas and Propagation)
In this paper, a kind of half-loop Yagi-Uda antenna made of high-permittivity dielectric is proposed to realize end-fire radiation. As two typical materials with high permittivity, low-loss zirconia ceramic and liquid pure water are here employed for the proposed antenna to attain high radiation efficiency and support the characteristic of pattern reconfigurability, respectively. The thin dielectric waveguide with high permittivity is here used as the metal wire of conventional wire antennas, due to its traveling-wave radiation under TM01 mode. The different radiation characteristics of the electrically small loop and full-wave loop antennas are discussed. And the dielectric large half-loop antenna with ground plane and bi-directional radiation is utilized to form a Yagi-Uda array for desired end-fire radiation. Moreover, circular loop elements are subsequently transformed into rectangular shape to reduce the profile of antenna and a comparison between the conventional metal Yagi-Uda antenna and the proposed dielectric one is provided. It is found that the dielectric parasitic element could play a more flexible role. Both ceramic and pure-water antenna prototypes are fabricated and tested. Measured results match the simulated ones well, which validates the predicted antenna performance.